Orthogonal spiral structures for energy harvesting applications: Theoretical and experimental analysis. (May 2018) - Santos, Auteliano Antunes Dos; Hobeck, Jared D.; Inman, Daniel J
The capture of energy from vibration of mechanical systems has been extensively studied with the goal of providing power for various microelectromechanical systems. The traditional cantilever beam approach was used as a starting design for more complex, multiple-beam structures like zigzag or spiral geometries. This work presents the orthogonal spiral structure, an alternative compact periodic structure for reduced frequency energy harvesting. The proposed orthogonal spiral structure design is inspired by a combination of zigzag and Archimedean spiral geometries. The orthogonal spiral structure takes advantage of a simple cantilever beam-based design as with the zigzag, but includes the compact concentric-type design of an Archimedean spiral. First, the fundamental frequency is estimated using a lumped parameter model for the substrate beam and the results are compared with experimental results for two different sizes of orthogonal spiral structures. Then, the same model is updated to include a layer of piezoelectric material and used to identify the strain nodes along each beam obtained from the first mode shape. Finally, electromechanical modeling is developed allowing for the evaluation of the energy harvested from base excitations. The results show that the orthogonal spiral structure can be used as an alternative to current energy harvesting systems for micro scale applications.